Functional comparison of anti-restriction and anti-methylation activities of ArdA, KlcA, and KlcAHS from Klebsiella pneumoniae - Chen, Huimin; Tao, Shuan; Li, Na; Wang, Fang; Wang, Lei; Tang, Yu; Liang, Wei (Frontiers in Cellular and Infection Microbiology, 2022)
Anti-restriction proteins are typically encoded by plasmids, conjugative transposons, or phages to improve their chances of entering a new bacterial host with a type I DNA restriction and modification (RM) system. The invading DNA is normally destroyed by the RM system. The anti-restriction proteins ArdA, KlcA, and their homologues are usually encoded on plasmid of carbapenemase-resistant Klebsiella pneumoniae. We found that the plasmid sequence and restriction proteins affected horizontal gene transfer, and confirmed the anti-restriction and anti-methylation activities of ArdA and KlcA during transformation and transduction. Understanding the molecular mechanism underlying the clinical dissemination of K. pneumoniae and other clinically resistant strains from the perspective of restrictive and anti-restrictive systems will provide basic theoretical support for the prevention and control of multidrug-resistant bacteria, and new strategies for delaying or even controlling the clinical dissemination of resistant strains in the future.